1986
DOI: 10.1080/07315724.1986.10720144
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis: an insulin-dependent disease?

Abstract: Evidence is reviewed that dietary habits in industrially developed countries, especially an increased frequency of ingestion of foods of high energy density, may contribute to excessive hepatic cholesterol synthesis and to a preponderance of lipogenic versus lipolytic effects on the arterial intima, thereby favoring the formation and progression of atheroma. These effects are mediated by the rise and fall of circulating insulin levels. The evidence is suggestive of the possibility that frequent and prolonged e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 47 publications
(48 reference statements)
0
21
0
Order By: Relevance
“…diabetes mellitus is approximately two to three times higher than that in normoglycemic individuals (53). Recent research has further shown that insulin enhances the proliferation of arterial smooth-muscle cells and stimu lates lipogenesis in arterial tissue (34). Not surprisingly, hyperinsulinemia has also been linked to an accentuated risk for acute myocardial infarction, even in nondiabetic men (24).…”
Section: Reduced Risk For Hypertension and Lowering Of High Blood Prementioning
confidence: 99%
“…diabetes mellitus is approximately two to three times higher than that in normoglycemic individuals (53). Recent research has further shown that insulin enhances the proliferation of arterial smooth-muscle cells and stimu lates lipogenesis in arterial tissue (34). Not surprisingly, hyperinsulinemia has also been linked to an accentuated risk for acute myocardial infarction, even in nondiabetic men (24).…”
Section: Reduced Risk For Hypertension and Lowering Of High Blood Prementioning
confidence: 99%
“…Behall et al (1989) also reported a lowering of blood triglycerides and cholesterol in subjects consuming high-amylose maize starch. The Ñat-tened insulin response observed with amylose may also be beneÐcial for hyperlipidaemic subjects because high insulin levels have been implicated in the development of thickened arterial walls and lesions (Ducimetiere et al 1980 ;Flodin 1986). Jenkins et al (1987) reported that products giving low glucose and insulin responses are e †ective in the treatment of both hyperlipidaemia and diabetes.…”
Section: Introductionmentioning
confidence: 98%
“…Elevated plasma glucose or insulin levels after a glucose load have been associated with non-insulin dependent diabetes [3] and cardiovascular diseases [4]. Low glycemic index foods or foods containing SDS maybe helpful in controlling and preventing these diseases.…”
Section: Introductionmentioning
confidence: 99%